Characteristics of multiple sclerosis in the Middle East with special reference to the applicability of international guidelines to the region. (2nd September 2014) - Al Tahan, Abdulrahman M.; Alsharoqi, Isa; Bohlega, Saeed A.; Dahdaleh, Maurice; Daif, Abdulkader; Deleu, Dirk; Esmat, Khaled; Giampaolo, Dominic; Freedman, Mark S.; Gwilt, Michael; Hosny, Hassan; Inshasi, Jihad S.; et al.
<x xml:space="preserve">Abstract</x> We have reviewed the clinical literature with reference to the local applicability of guidelines for the diagnosis and management of multiple sclerosis (MS) in the Middle East. There is a substantial burden of MS in the region: the prevalence of the disease appears to have increased markedly in recent decades, with a faster rate of increase in female vs. male patients. The aetiology and presentation of MS appears to be broadly similar in the Middle East to that in other regions. Interferon-β is the most commonly used treatment for MS in the Middle East, as elsewhere, although it is unclear to what extent economic constraints act as a barrier to accessing this treatment. Similarly, limited available data suggest that the availability of MRI scanners appears to be lower in the Middle East than in more developed nations. Little is known concerning other potential barriers to treatment. There is a need for further research on aspects of management of MS beyond the pharmacological aspects of treatment to assess fully the potential barriers to the adoption of international guidelines for the diagnosis and management of the disease in the Middle East.